Study of the interfacial adhesive strength of a heat‐shrinkable multilayer film. Issue 3 (1st January 2021) - Nishitsuji, Shotaro; Shinozaki, Chie; Miyata, Ken; Yamada, Shinya; Yoshida, Jun
Abstract: A heat‐shrinkable multilayer film is widely employed as labels of plastic bottles. A new heat‐shrinkable multilayer film without an adhesive layer was designed in this study. The interfacial adhesive strength between the layers was controlled to avoid layer separation. We assumed a polyethylene terephthalate glycol‐modified (PETG)/styrene‐co‐butadiene block copolymer/PETG shrinkable film substitute as the general poly(ethylene terephthalate) (PET)/polystyrene/PET shrinkable film. The interlayer adhesive strength between the layers was retained for industrial utilization even after drawing. Additional polybutadiene (PB) infiltrated the butadiene layer in the microphase‐separated structure. Further addition of PB could not infiltrate the butadiene layer. The excessive PB contents coexisted with the interface between the layers, as observed by transmission electron microscopy (TEM). The segregated PB enhanced the interfacial adhesive strength. We concluded that the selective distribution of adhesive functional materials along the interface could appropriately retain its adhesive strength. Abstract :